Factors Influencing Investment Decisions in Gold - Thapa, Bishesh; Shah, Ajay Kumar (Journal of Business and Social Sciences Research, 2020)
The paper aims to evaluate the various factors influencing investment decisions in gold. Six influential factors such as price of gold, secured investment, liquidity need, social status, advertisement and influences and demand of gold were used and their relation with investment decision in gold was tested. The study is based on descriptive research design and uses the primary data obtained by a structured questionnaire for quantitative analysis. Convenient sampling method was used and sample size of 160 respondents was taken from Kathmandu valley. The study uses descriptive statistics, t-test, and correlation to show the important influential variable and relation with investment decision. Among all the influential variables, liquidity need and social status shows the highest mean value which indicates strong agreement towards reason for investing in gold whereas advertisement and influences has lowest agreement. However, when it comes to relationship of different factors with investment decision on gold then, secured investment has the highest correlation value with the investment decision in gold. Moreover, the results showed that there is positive significant relationship between all the contextual variables and investment decision.